4-[(2E)-2-(4-Chlorobenzylidene)hydrazinylidene]-1-methyl-1,4-dihydropyridine monohydrate - Aydin, Abdullah; Akkurt, Mehmet; Alptuzun, Vildan; Büyükgüngör, Orhan; Holzgrabe, Ulrike; Radacki, Krzysztof (International Union of Crystallography (IUCr), 2010)
In the title compound, C(13)H(12)ClN(3)·H(2)O, the organic mol-ecule is almost planar, with a dihedral angle of 3.22 (10)° between the benzene and pyridine rings. The crystal structure is stabilized by O-H⋯N and C-H⋯O hydrogen bonding and π-π stacking inter-actions [centroid-centroid distances = 3.630 (1) and 3.701 (1) Å].
Keywords: Crystallography; QD901-999; Organic Papers